Effect of Combined Use of Oral Prednisolone and Propranolol in the Treatment of Infantile Hemangioma: A Single Center Study - Chowdhury, Tahmina Akhter; Hoque, Md Saiful; Hoque, Roksana; Nandy, Alok (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background : Infantile hemangioma is a benign vascular tumor. Considerable controversy exists as to the management of hemangiomas. The purpose of this study was to see the efficacy and safety of orally administered prednisolone and propranolol in combination for treatment of potentially disfiguring or functionally threatening hemangiomas Materials and methods: In this prospective study, thirty two patients of hemangioma with age range of 1 month to 5 years were included who were treated with oral propranolol (1 mg/kg/ day in two divided doses) and oral prednisolone (2 mg/Kg/ day in single dose) in combination. This study was conducted in outpatient Department of Pediatric Surgery of Chattogram Medical College Hospital from January 2016 to December 2017. Changes in size and color of lesions were the two evaluating factors to see the efficacy of the treatment. Therapeutic response was graded as excellent, good, poor and no response. Results: Overall therapeutic response was 92.62% (29 patients). Excellent response was noted in 21 patients (65.62%) and in 3 patients (9.38%) there was no response. Range of treatment period was 6 to 20 weeks. No side effects except excessive weight gain was noted (6.25%). Conclusion: Combined use of low dose oral prednisolone and propranolol is more effective and safe for treatment of hemangioma. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 23-26